The Development of Interactive CD Learning for Autism Children - Ahmad, Ibrahim; Bakar, Norasiken (Malaysian Educational Technology Association (META), Educational Technology Division, Ministry of Education Malaysia, 2009)
This paper describes on how the Interactive Cd Learning for Autism Children has been design and develops. This is the project to help the children as a difficulties learner like an autism childre using computer based approach. The techniques are applied in this interactive CD is Discrete Trial Training (DTT) which are also known Applied Behavioral Analysis (ABA) as one of the technique as suitable for autism children treatment. Based on the case studies, the information collected has become a guidance to design a courseware. The theme for "Science, Social, & Environment Components" have been chosen.